Digitaria sanguinalis seed dormancy release and seedling emergence are affected by crop canopy and stubble. (25th November 2019) - Oreja, F H; Batlla, D; de la Fuente, E B
Summary: Digitaria sanguinalis is a troublesome annual weed that causes important yield losses in different crops. Despite this, there is scarce information about different aspects of its biology under field conditions. New knowledge about the establishment process of this species will be of paramount importance in order to maximise the effectiveness of weed management. The aims of this paper were to evaluate the effect of stubble found on the surface on seed dormancy levels through the season, the effects of stubble and soyabean crop canopy on seedling emergence and to determine the field emergence pattern as a consequence of seed dormancy level at dispersal time. Seeds on the soil surface, which showed a high dormancy level at the beginning of autumn, were released from dormancy by low winter temperatures and germinated during spring as temperatures rose, showing a transient surface seedbank. Seeds covered by stubbles had delayed the emergence in the field due to lower alternating temperatures perceived by the surface seedbank. On the other hand, the presence of a soyabean crop and stubble together reduced the number of seedlings. Seeds with a high dormancy level at dispersal time showed a delayed emergence in the next season when compared with seeds with a lower dormancy level. However, the final number of seedlings was similar. Both stubble on surface and crop canopy are useful factors to lessen and delay the seedling emergence allowing the design of weed management strategies in order to diminish the population levels of this species.